Home garden / Wan Noorli Razali - Razali, Wan Noorli (Academy of Language Studies, 2023)
It would be a blessing to have ample room in our backyard or the front compound for all our plants to be planted on the ground. They can grow on wide, rich garden beds. Well, though we can do this, planting in pots still adds artistic touch to the garden and our surroundings. The combination of both may work better in most home gardens. With the advent of technologies and ease of getting ourselves all the garden needs at just one click in the comfort of our home, we may still be puzzled on which the right ones are. In this issue, we will see some tips on choosing the right pot for our plant. Let us start with the basic and the most important aspect of choosing a pot. Pot with drainage holes is required to ensure you can grow a healthy plant. Now, we may wonder if one single drainage hole is enough for a pot. It is not a problem to get a pot with a single drainage hole in the middle or one with more drainage holes if the hole works well to drain excessive water from the pot. Secondly, it is important for us to ensure we buy the right pot size for our plant. The basic rule is that we must get a pot that is an inch to 4 inches wider than the diameter of the plant's root mass.